Development and Evaluation of “Let’s Learn KENALAN”: A Canva-Based Interactive Media for IPAS Instruction in Grade III - Risma Aulia; Akhmad Junaedi (STAI Hubbulwathan Duri, 2025)
This study addresses the limited use of interactive media in IPAS (Natural and Social Sciences) instruction at the elementary level, which often leads to low student engagement. To enhance learning outcomes and motivation, this research aimed to develop and evaluate the effectiveness of an interactive Canva-based learning media titled Let’s Learn KENALAN, focusing on the topic of natural and artificial appearances for third-grade students. The study employed a Research and Development (RD) approach using the ADDIE model, which comprises five stages: Analysis, Design, Development, Implementation, and Evaluation. The participants were 20 third-grade students from Patemon 02 Elementary School, with 6 students involved in a small-scale trial and 14 in a large-scale trial. Data collection included expert validation, pre- and post-tests, and user questionnaires. Validation results showed high feasibility with scores of 98.3% from subject matter experts, 92.3% from media experts, 93.4% from teachers, and 92.7% from students, averaging 94.1%. The effectiveness test using the N-Gain formula revealed improved learning outcomes, with an N-Gain score of 0.734 (moderate category) in the small-scale trial and 0.7908 (high category) in the large-scale trial. The findings suggest that Let’s Learn KENALAN is both pedagogically sound and effective in improving students’ understanding of IPAS content. The media fosters greater engagement and supports active learning. It holds strong potential for broader application in elementary classrooms to enhance science and social studies instruction.